THE CONSTRUCTIVIST APPROACH AS THE MOST CRUCIAL PRINCIPLE IN THE DEVELOPMENT OF A CURRICULUM FOR STUDYING ENGLISH FOR SPECIFIC PURPOSES IN A MODERN UNIVERSITY - Grigoryan, Lusine (Foreign Languages for Special Purposes, 2024)
The article explores the specifics of the constructivist approach in education and discusses the objectives of learning a foreign language. Constructivism is an educational theory and approach to learning that suggests learners actively construct their own knowledge and understanding of the world through their experiences, interactions, and reflections. The key principles of constructivism emphasize the learner’s role in the learning process and the importance of meaningful, rich experiences. The constructivist approach emphasizes active learning, critical thinking, and problem-solving. In the context of developing a curriculum for studying English for specific purposes (ESP) in a modern university, the constructivist approach would involve: contextualized learning: designing the curriculum based on the specific needs and contexts of the learners. For English for specific purposes, this could mean tailoring the content to the professional or academic fields relevant to the students, such as business, science, or technology; interactive learning activities: integrating activities that encourage students to actively engage with the material. This could include group discussions, case studies, real-world projects, and simulations relevant to their specific field; authentic materials: using authentic materials like industry reports, academic journals, or workplace documents to expose students to the language they will encounter in their future professions; student-centered learning: shifting the focus from the teacher as the sole source of knowledge to students taking an active role in their own learning. This might involve projects, research, and presentations related to their specific field; assessment for learning: implementing assessments that measure not only language proficiency but also the application of language skills in real-world situations. This could involve practical tasks, presentations, or portfolios demonstrating their understanding in a professional context. The application of the constructivist approach in ESP aims to make the learning experience more meaningful and relevant to students’ future endeavors, fostering a deeper understanding of the language within the specific context in which they will use it.